2016
DOI: 10.1071/an14755
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell quality: a comparison between Fayoumi, Gimieizah and Brown Hy-Line strains for mechanical properties and ultrastructure of their eggshells

Abstract: This experiment was designed to study the relationship between mechanical properties and ultrastructure of three genetic groups (Fayoumi, Gimieizah and Brown Hy-Line strains). To assess eggshell mechanical parameters a total of 120 eggs from each strain was used. This study suggested predicting the mechanical properties and ultrastructure of eggshells when egg weight was equal for the three strains (39.8 g). There was a significant difference among strains for shell thickness, eggshell breaking strength and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In addition, hatchability correlates positively with eggshell thickness ( Liao et al., 2013 ). Eggshell structural and textural features that are important for shell strength, such as the density of mammillary knobs, the effective thickness of the mastoid layer, and the width of the mastoid gap, are closely related to eggshell strength ( Radwan, 2015 ). Improved eggshell strength can effectively reduce the loss of eggs in egg marketing activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hatchability correlates positively with eggshell thickness ( Liao et al., 2013 ). Eggshell structural and textural features that are important for shell strength, such as the density of mammillary knobs, the effective thickness of the mastoid layer, and the width of the mastoid gap, are closely related to eggshell strength ( Radwan, 2015 ). Improved eggshell strength can effectively reduce the loss of eggs in egg marketing activities.…”
Section: Discussionmentioning
confidence: 99%
“…Low density of the mammillary knobs reduces the binding force between the mammillary knob and the eggshell membrane and weakens eggshell strength. In general, the constant size and shape of the mammillary knob and the strong bond between the knobs and the shell membrane resulted in high eggshell strength ( Dunn et al, 2012 ; Radwan, 2016 ). In the classification of mammillary types, Fathi et al (2007) reported that type A mammillary bodies were even in size and distribution and rounded so that there can be maximum attachment to the fibers of the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Low quality eggshells tend to have an irregular, uneven, or incompletely formed mammillary core arrangement. The mammillary knob abnormalities often are manifested as reduced thickness or increased porosity ( Dunn et al, 2012 ; Radwan, 2016 ). The palisade layer is made of calcite crystals in which an organic matrix is embedded, which accounts for the most of thickness of the eggshell ( Fathi et al, 2007 ; Nys and Gautron, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, eggshell ultrastructure in aged hens was characterized by thicker mammillary layer, thinner effective layer and less frequency of early fusion. The thickness and proportion of effective layer were the major ultrastructural characteristics determining shell strength and a reduction in its thickness could compromise shell strength conducing to a higher incidence of breakage [25]. Stress concentrations would occur more frequently and rapidly in the site where the fusion of adjacent mammillary columns was delayed or where structural abnormalities arose.…”
Section: Discussionmentioning
confidence: 99%